Kendala Pemahaman dan Kompetensi Guru dalam Mengimplementasikan Pendidikan Inklusi pada Pembelajaran Ilmu Pengetahuan Alam dan Ilmu Pengetahuan Sosial di Kota Pariaman - Syiti Mutia Hasnan; Asep Supena; Totok Bintoro; Riswandi (Postgraduate, University of Mataram, 2025)
This study aims to analyze the constraints of teachers' understanding and competence in implementing inclusive education in Natural and Social Science Learning at SDN 13 Kampung Baru, Pariaman City. This study used a descriptive qualitative approach with data collection methods in the form of in-depth interviews, classroom observations and document analysis. The research subjects consisted of five class teachers, one IPAS subject teacher, and one special assistant teacher (GPK). The results showed that 80% of teachers experienced problems in understanding the concept of inclusive education, especially related to the adaptation of IPAS materials for students with special needs. In addition, 70% of teachers admitted to having difficulties in implementing inclusive teaching methods, such as the use of appropriate learning media and experiential learning strategies. The inhibiting factors included a lack of training in inclusive education (90%), a lack of collaboration with GPK (60%) and limited supporting facilities at school (75%). This study recommends organizing intensive training to improve teachers' competencies, procuring inclusive learning media and increasing collaboration between classroom teachers and GPKs. The results of this study are expected to be a reference in developing more inclusive and effective Natural and Social Science Learning strategies in primary schools.